2015
DOI: 10.1186/s12889-015-2376-z
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviours among electronic waste workers in Ghana

Abstract: BackgroundElectronic waste workers are prone to various illnesses and injuries from numerous hazards thus the need for them to seek health care. The aim of this study was to describe health-seeking behavior, and social and other factors affecting this behavior, among electronic waste workers at Agbogbloshie, Accra, Ghana.MethodsIn-depth interviews were conducted and analyzed qualitatively from a grounded theory perspective.ResultsWorkers experienced various kinds of ailments. These included physical injuries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 24 publications
8
65
1
4
Order By: Relevance
“…The study by Asante et al (2012) on 20 male workers at Agbogbloshie established that toxic metal exposures occur, though this work was limited by a relatively low sample size, a single biomarker studied, and lack of key socio-demographic and occupational characteristics. Here we build upon the work by Asante et al (2012) as well as previous studies by our team at Agbogbloshie (Wittsiepe et al, 2015; Feldt et al, 2014; Akormedi et al, 2013; Asampong et al, 2015; Burns et al, 2016), and capitalize upon our growing collaborative relationship with the Greater Accra Scrap Dealers Association. The socio-demographic characteristics of the study population here is similar to previous studies at Agbogbloshie by our research team and others thus enabling comparisons to be made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Asante et al (2012) on 20 male workers at Agbogbloshie established that toxic metal exposures occur, though this work was limited by a relatively low sample size, a single biomarker studied, and lack of key socio-demographic and occupational characteristics. Here we build upon the work by Asante et al (2012) as well as previous studies by our team at Agbogbloshie (Wittsiepe et al, 2015; Feldt et al, 2014; Akormedi et al, 2013; Asampong et al, 2015; Burns et al, 2016), and capitalize upon our growing collaborative relationship with the Greater Accra Scrap Dealers Association. The socio-demographic characteristics of the study population here is similar to previous studies at Agbogbloshie by our research team and others thus enabling comparisons to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Most workers live at Agbogbloshie resulting in continual exposure to hazards, and the region and its workers lack basic health and welfare services (Asampong et al, 2015). Despite such concerns, there has been little investigation of the job activities performed at Agbogbloshie.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we are aware, the only publication on occupational injuries among informal e-waste workers is one qualitative study in Ghana, which studied the health-seeking behaviour of the e-waste workers when they are sick or sustain injury at work 19. The first step to injury prevention is knowing the magnitude of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…They however observed that the research focusing on evaluating the design of the e-waste supply chain was moving towards a more holistic framework for sustainability assessment. A further review made within this study showed that: ‚ e-waste recycling programs and take-back schemes have been assessed against more than one bottom line of sustainability, such as [13,14] ‚ sustainability-related assessments on e-waste treatment processes found in the literature focused on environmental assessments or alternatively on social sustainability assessments; the former have been primarily delivered through a life-cycle assessment methodology, as in [15,16], whereas the latter, which focused primarily on health conditions of workers, have been made through in-depth interviews [17] and reporting of health-related indicators related to human toxicity [18].…”
Section: Sustainable E-waste Management Systemsmentioning
confidence: 99%